PENGARUH KEPEMILIKAN KELUARGA TERHADAP TINDAKAN PAJAK AGRESIF DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia Tahun 2010 - 2013) - Wahyu Tri Utami; Hendri Setyawan (Conference In Business, Accounting, And Management (CBAM), 2015)
The present research aims to investigate the effect of corporate governance on the relationship between family ownership and tax aggresiveness as studied by Sari and Martani (2010). We test three hyphothesis namely the effect of family ownership on tax aggresiveness, the effect of corporate governance on tax aggresiveness, and the moderating effect of corporate governance on the relationship between family ownership and tax aggresiveness. We used newer data set than Sari and Martani (2010). We purposively selected data sample from manufacturing firms listed at Indonesian Stock Exchange in the period 2010 to 2013. Using multiple regression analysis, we couldn’t find robust findings on the relationship between variables. The result consistent with Sari and Martani (2010). Future research could use different proxies for the variables such as corporate governance indices.Keywords: family ownership, corporate governance, tax aggresiveness